2019
DOI: 10.3389/fneur.2019.00163
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Meningitis Presenting With Acute Parkinsonism and Protracted Non-convulsive Seizures: An Unusual Case Presentation and Review of Treatment Strategies

Abstract: Rheumatoid meningitis is a rare complication of rheumatoid arthritis (RA). It is associated with substantial morbidity and mortality. The condition may present in a variety of ways and is therefore diagnostically challenging. Uncertainty still exists regarding the optimal treatment strategy. Herein, we describe the case of a 74-year-old man with a history of well-controlled seropositive RA on low-dose prednisone, hydroxychloroquine, and methotrexate. The patient presented with a several-month history of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…While common neurological symptoms like headaches, seizures, focal neurological deficits, altered mental condition and cranial nerve palsies that present as blindness or sensorineural deafness were reported over the years [12,14], some rare symptoms have been described in the recent times which include neuropsychiatric presentation [5] and acute parkinsonism [15]. Due to these varied neurological symptoms and a multitude of etiologies for pachymeningitis, diagnosis of rheumatoid meningitis is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While common neurological symptoms like headaches, seizures, focal neurological deficits, altered mental condition and cranial nerve palsies that present as blindness or sensorineural deafness were reported over the years [12,14], some rare symptoms have been described in the recent times which include neuropsychiatric presentation [5] and acute parkinsonism [15]. Due to these varied neurological symptoms and a multitude of etiologies for pachymeningitis, diagnosis of rheumatoid meningitis is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for RA was continued or was changed to rituximab which successfully managed the RA progression [1,3,7,25,35]. Elevated serum ACE and β-2 microglobulin were reported by Pellerin et al [15] and McKenna et al [8] although, these findings haven't been clearly associated with RM [8,15]. Some patients had pulmonary manifestations in the form of nodules or pleural effusions which were attributed as extra-articular manifestations of RA after examinations [22,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…Review of literature showed only n=13 cases of rheumatoid nodules in the CNS reported since 2000 4–15. These are presented in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to diseasemodifying therapy, there is evidence that the transient neurological deficits in RA meningoencephalitis should be treated with antiepileptic drugs (AEDs). Even episodes that are not clearly electroclinical seizures seem to respond to AED's [34,39]. Evidence for treatment of neurosarcoidosis (NS) is based on cases series and expert opinion [40•, 41-43].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Less than half of patients with CNS disease have active synovitis and 34% of patients had no history of RA prior to diagnosis [ 33 ]. The most common brain MRI finding is nodular patchy or lepto-meningeal thickening and enhancement, and biopsy is the gold standard for diagnosis [ 2 •, 34 ].…”
Section: Inflammation Of the Central Nervous System From Rheumatologimentioning
confidence: 99%